Seawater desalination by reverse osmosis: Current development and future challenges in membrane fabrication – A review - Lim, Yu Jie; Goh, Kunli; Kurihara, Masaru; Wang, Rong (Journal of membrane science, 2021)
Seawater reverse osmosis (SWRO) is the key technology driving an energy-efficient and cost-effective desalination process. At the center of this technology are the thin film composite (TFC) membranes, which not only promise a stable operation but also high separation performances. The objective of this review is to consolidate recent advances in SWRO membranes from the standpoint of membrane materials, fabrication methodologies and applications. First, the thermodynamic limit and energy consumption of SWRO desalination are reviewed, before we discuss the current status of SWRO membranes, highlighting the four main challenges to date – permselective tradeoff, relatively low single-pass boron rejection, membrane fouling and poor chlorine resistance. Thereafter, a comprehensive review of the membrane development is presented. We examine findings reported in research papers and patents, and various methods to achieve SWRO membranes of higher permselectivity, boron rejection, and chlorine resistance as well as lower fouling propensity. Key insights from the membrane industry are also furnished. Then, we put together an outlook, featuring our perspectives on SWRO membrane development. Empirical data in this review are collated into an upper-bound relationship, which is tailored specifically for SWRO membranes and expected to provide benchmarking for future SWRO membrane development. Since the traits of SWRO membranes are unique from those of brackish water RO (BWRO) membranes, we also distinguish the methods used for SWRO membrane fabrication to help zero in on the correct strategies, and provide insights for advancing new membrane designs. Overall, this review sums up the current state-of-the-art SWRO membranes, looking at the array of fabrication methods used thus far, and putting into perspective critical strategies to realize the next-generation TFC membranes that can address the future demands of SWRO and deliver a more competitive desalination process. [Display omitted] •Recent advances in SWRO membrane are collated from papers and industrial patents.•Current status and future outlook of SWRO membrane industry are discussed.•A permselectivity upper bound is established specifically for SWRO membranes.•The upper bound is given by A/B = 46.75A−1.72 (A/B in bar−1 and A in Lm−2h−1 bar−1).•A roadmap for SWRO membrane fabrication is proposed (short/long-term strategies).